CORRELATION AMONG THE STUDENTS’ READING HABITS, PERSONALITY, AND READING COMPREHENSION - Irfan, Luthfia Nurhanisa; Amin, Fatimah Hidayahni; Salija, Kisman (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research aimed to find a significant correlation among the reading habits, personality, and reading comprehension of students at SMA Negeri 6 Bulukumba. This research applied a quantitative method with a correlational design. There were 35 students as the sample, taken by using the cluster random sampling technique. The data was collected through reading habit and personality questionnaires and reading tests. The results of this research according to correlational analysis showed there was a significant correlation between the independent variables (students' personality and reading habits) and the dependent variable (students' reading comprehension). The sig. F. change value of this research was 0.044 which was less than 0.05 and the R value of 0.422 showed a 'medium' correlation. This research indicated that extroversion and introversion did not significantly impact reading comprehension directly, the combination of reading habits and personality traits showed a meaningful correlation with reading comprehension.